The fog of short videos among adolescents: the interwoven influence of family environment, psychological capital, and self-control - Qing Wang; Yimeng Guo; Zhensong Lan; Huaqiang Liu (Humanities & Social Sciences Communications)
Abstract Short videos, with their brevity and high entertainment value, attract many adolescent users. However, prolonged viewing may negatively impact adolescents’ cognitive development, especially self-control and academic performance. This study explores the impact of the family environment on adolescents’ addiction to short videos and reveals the intrinsic role of psychological capital and self-control in the relationship between the family environment and adolescents’ short video addiction. Based on ecosystem theory, a hypothetical model was constructed in which psychological capital and self-control serve as chained mediators in the influence of the family environment on short video addiction. Revised scales for family environment, psychological capital, self-control, and short video addiction were used to conduct a survey among 1,735 middle school students from five provinces in China (51.7% male; M age = 15.2, SD = 1.8). This study found that: (1) A positive family environment, psychological capital, and self-control are significantly negatively correlated with adolescents’ short video addiction; (2) The mediating effect of psychological capital between the family environment and short video addiction is not significant; (3) Self-control has a significant mediating effect between the family environment and short video addiction (6.8%); (4) Psychological capital and self-control have a significant chained mediating effect between the family environment and short video addiction (12.8%). The family environment has a significant impact on adolescents’ short video addiction. Close family relationships and rich family recreational activities help reduce the risk of addiction. Psychological capital and self-control play important mediating roles in the relationship between the family environment and short video addiction. Enhancing adolescents’ psychological capital and self-control abilities can effectively prevent and intervene in addiction issues.